DYNAMICS OF HEMOSTASIS AND NEUTROPHIL FUNCTIONAL ACTIVITY CHANGES IN PATIENTS WITH VARIOUS SENSITIVITY TO ACETYLSALICYLIC ACID IN ACUTE MYOCARDIAL INFARCTION - I. Yu. Grinshtein; A. A. Savchenko; Yu. I. Grinshtein; N. Yu. Shimokhina; M. M. Petrova; I. I. Gvozdev (Российский кардиологический журнал)
Aim. To study in dynamics the specifics of hemostasis and functioning of neutrophilic granulocytes in patients with acute myocardial infarction (MI) sensitive and resistant to acetylsalicylic acid (ASC).Material and methods. Totally, 53 patients included during first 24 hours from MI onset. Controls were 50 relatively healthy volunteers. All patients before treatment and revascularization were assessed for resistance to ASC and selected to groups as sensitive (SASC) and resistant (RASC). In complex therapy there was double antiplatelet therapy (ASC+clopidogrel). The parameters of vessel-platelet and plasma hemostasis were assessed. Via the chemiluminescent analysis we studied functional activity of neutrophils.Results. In RASC patients with MI on 1st and 10th day we found increased ADP aggregation of thrombocytes (ADP 0,1 mcM) and increase of von Willebrand factor. On 10th day in SASC patients there was decrease of ADP aggregation (ADP 5 mcM), von Willebrand factor increases. Not related to ASC sensitivity, in MI patients there is increase of SFMC, thrombin time is increased and D-dimer is low. Kinetics of chemiluminescence of neutrophils in MI patients differs from controls only by increased time of reached maximum. In ASC resistant patients on 1st day of evaluation there is decrease of neutrophil activation index, which gets to normal by 10th day of treatment.Conclusion. In RASC MI patients there is increased ADP aggregation of platelets, decrease of platelets number and increase of von Willebrand factor levels. Thrombosis risk in RASC patients on 10th day of treatment is caused by remaining disordered vessel-platelet hemostasis and increased spontaneous platelets aggregation. Plasmatic hemostasis on 1st and 10th days of MI shows activated onset of clotting with increase of clotting duration and significant decrease of D-dimer. In MI there is slowed velocity of development of “respiratory boost” in neutrophilic granulocytes that is probably related to compensatory processes in organism and double antiplatelet therapy which is antiinflammatory as well.